2016
DOI: 10.1177/0961203316651748
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and new detection system of autoantibodies in myositis with interstitial lung disease

Abstract: Anti-aminoacyl-tRNA synthetase (ARS) and anti-melanoma differentiation-associated gene 5 ( MDA5) antibodies are closely associated with interstitial lung disease in polymyositis and dermatomyositis. Anti-ARS-positive patients develop common clinical characteristics termed anti-synthetase syndrome and share a common clinical course, in which they respond well to initial treatment with glucocorticoids but in which disease tends to recur when glucocorticoids are tapered. Anti- MDA5 antibody is associated with rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 76 publications
1
83
1
Order By: Relevance
“…MSAs are detected in 45-85% of adult IIM patients and in 50-70% of juvenile IIM (JIIM) patients [1][2][3][4][5][6][7][8]. In adult patients, anti-ARSs are most frequently detected (20-40% of IIM cases) followed by anti-MDA5 (8-20%), anti-SRP (3-10%), anti-TIF1-c (5-7%), anti-Mi-2 (3-8%) and anti-NXP2 (5-8%) [2,9]. The most frequent MSAs in JIIM are anti-NXP2 (15-23%), anti-TIF1-c (15-35%) and anti-MDA5 (7-28%); in contrast, anti-ARSs are relatively rare (2-8%) [5].…”
Section: Myositis-specific Autoantibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…MSAs are detected in 45-85% of adult IIM patients and in 50-70% of juvenile IIM (JIIM) patients [1][2][3][4][5][6][7][8]. In adult patients, anti-ARSs are most frequently detected (20-40% of IIM cases) followed by anti-MDA5 (8-20%), anti-SRP (3-10%), anti-TIF1-c (5-7%), anti-Mi-2 (3-8%) and anti-NXP2 (5-8%) [2,9]. The most frequent MSAs in JIIM are anti-NXP2 (15-23%), anti-TIF1-c (15-35%) and anti-MDA5 (7-28%); in contrast, anti-ARSs are relatively rare (2-8%) [5].…”
Section: Myositis-specific Autoantibodiesmentioning
confidence: 99%
“…Anti-ARS-positive patients develop common clinical manifestations, characterized by myositis, ILD, arthritis, fever, Raynaud's phenomenon and mechanic's hand, which is called 'anti-synthetase syndrome (ASS)' [22]. Anti-ARSs have a strong association with ILD because 70-95% of anti-ARS-positive patients [21,23,24] have ILD and 40-55% of PM/DM patients with ILD are positive for anti-ARSs [2,25]. Anti-ARS-positive ILD tends to be diagnosed at the same time or even before the development of myositis [22].…”
Section: Anti-arsmentioning
confidence: 99%
“…Recently, some case reports have suggested that a combined immunosuppressive therapy might be efficacious; this type of therapy includes high‐dose GCs, calcineurin inhibitors (CNIs), and intravenous cyclophosphamide (IV CYC), which are administered beginning in the early phase of rapidly progressive ILD with DM/CADM . In addition, we have observed the effectiveness of such combination therapy in the early stage of rapidly progressive ILD in Japanese patients with anti–MDA‐5–positive DM/CADM, compared to those receiving step‐up therapy (75% versus 29%) at our hospital . However, there has not been a prospective trial examining the efficacy and safety of this combination therapy.…”
Section: Introductionmentioning
confidence: 98%
“…Anti-MDA5 positivity was reported to be associated with a specific presentation of CADM featuring painful ulcerations over extensor surfaces and nailfolds, hyperferritinemia, and frequent treatment-resistant, rapidly progressive ILD associated with poor prognosis 3, 13. Interestingly, MDA5 protein functions as an intracellular pathogen sensor involved in the recognition and mounting of immune response to viral RNA 3, 4. Hence, there could be an association between CADM and viral infections perhaps explaining the incidence of ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically amyopathic DM (CADM) accounts for approximately 20% of all cases and is diagnosed based on the presence of pathognomonic cutaneous involvement 2, 3. Antibody against melanoma differentiation–associated protein 5 (MDA5) was recently found to be specific for CADM associated with rapidly progressive interstitial lung disease (ILD) 4 . To our knowledge, there are no other cases of MDA5-positive CADM in an HIV-positive patient.…”
Section: Introductionmentioning
confidence: 99%